EARNING MANAGEMENT: ANALISIS CORPORATE GOVERNANCE PADA PERUSAHAAN SEMEN DI INDONESIA - Yanuar Trisnowati (Jurnal Ekonomi dan Manajemen, 2016)
Earnings management is interference management in the preparation process of financial statements that aim to be reported to shareholder. Earnings management can reduce the credibility of financial statements because it does not showed actual condition of the company. The shareholder is possible will take a wrong decision because they obtain wrong financial information. The purpose ofthis study is to analyze the impact of good corporate governance and firm size to earnings management at 82 manufacturing company in Indonesia Stock Exchange at 2012 until 2014. The dependent variable in this study is earnings management. The independent variable are managerial ownership, institutional ownership, proportion of independent commissioner, and firm size. To find the impact of variable, this study used multiple liner regression. The result of regression analysis showed that the variable managerial ownership, institutional ownership, and firm size had not significant effect to earnings management. Variable proportion of independent commissioner had significant effect to earnings management.